Transcriptome and metabolome profiling to elucidate the mechanism underlying the poor growth of Streptococcus suis serotype 2 after orphan response regulator CovR deletion - Zong, Bingbing; Xiao, Yong; Li, Rui; Li, Huanhuan; Wang, Peiyi; Yang, Xiaopei; Zhang, Yanyan (Frontiers in Veterinary Science, 2023)
The deletion of orphan response regulator CovR reduces the growth rate of Streptococcus suis serotype 2 (S. suis 2). In this study, metabolome and transcriptome profiling were performed to study the mechanisms underlying the poor growth of S. suis 2 caused by the deletion of orphan response regulator CovR. By comparing S. suis 2 (ΔcovR) and S. suis 2 (SC19), 146 differentially accumulated metabolites (upregulated: 83 and downregulated: 63) and 141 differentially expressed genes (upregulated: 86 and downregulated: 55) were identified. Metabolome and functional annotation analysis revealed that the growth of ΔcovR was inhibited by the imbalance aminoacyl tRNA biosynthesis (the low contents of L-lysine, L-aspartic acid, L-glutamine, and L-glutamic acid, and the high content of L-methionine). These results provide a new insight into the underlying poor growth of S. suis 2 caused by the deletion of orphan response regulator CovR. Metabolites and candidate genes regulated by the orphan response regulator CovR and involved in the growth of S. suis 2 were reported in this study.